When the Midline Diastema Is Not Characteristic of the “Ugly Duckling” Stage - Orlando Motohiro Tanaka; Alessandro Yuske Kusano Morino; Oscar Fernando Machuca; Neblyssa Ágatha Schneider (Case Reports in Dentistry)
This case report presents the interceptive orthodontic treatment of a 9-year, 5-month-old boy with class I malocclusion, a 9.0-mm maxillary midline diastema, and deviation from the midline. The treatment goals were to decrease the magnitude of the diastema and to simulate the characteristics of the “ugly duckling” stage. Braces were placed on the first molars and the maxillary central incisors. The biomechanics of the anchors on the first molars elicited substantial mesial movement of the left central incisor to match the midline. A flat wire segment was bonded onto the palatal surface of the central incisors for retention.